A hypoxia-on-a-chip platform for modeling ischemic arrhythmogenesis and evaluating the effects of levosimendan and OR-1896 on ischemic human iPSC-derived cardiomyocytes - Gaballah, Mahmoud; Walls, Kaisla; Zakzook, Fatma; Kreutzer, Joose; Levijoki, Jouko; Aalto-Setälä, Katriina (Frontiers in Bioengineering and Biotechnology, 2025)
Acute hypoxia is a major contributor to cardiomyocyte damage and dysfunction in ischemic heart disease, and the effective therapeutic strategies remain limited. Levosimendan, a calcium sensitizer with both inotropic and vasodilatory effects, along with its active metabolite OR-1896, is utilized in the treatment of acute heart failure. In this study, we investigated the cardioprotective and antiarrhythmic effects of levosimendan and its metabolite OR-1896 under hypoxic conditions using human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). hiPSC-CMs were exposed to acute hypoxia and treated with levosimendan or its metabolite OR-1896. Structural integrity was assessed via immunostaining and electron microscopy imaging. Calcium transient abnormalities were evaluated using live-cell imaging. Hypoxia-induced injury was further assessed by measuring cardiac biomarkers and gene expression profiling of hypoxia-associated pathways. Hypoxia induced significant structural damage, including sarcomere disorganization, mitochondrial cristae fragmentation, and nuclear shrinkage, accompanied by increased release of cardiac biomarkers. Hypoxia also upregulated genes associated with the hypoxia response, oxidative stress, and apoptosis, while disrupting calcium handling and increasing arrhythmic events. Treatment with levosimendan and its metabolite OR-1896 preserved cellular structure, reduced biomarker release, and stabilized calcium transients, significantly reducing hypoxia-induced arrhythmogenesis. Both compounds also modulated gene expression, downregulating hypoxia-responsive and oxidative stress markers, and inhibiting apoptotic pathways. Notably, the metabolite OR-1896 exhibited protective effects comparable to or even greater than those of levosimendan. This study provides the first comprehensive evidence of the cardioprotective and antiarrhythmic properties of levosimendan’s metabolite, demonstrating its ability to reduce hypoxia-induced cellular injury and correct abnormal Ca2+ transients. These findings highlight the therapeutic potential of levosimendan and its clinically significant long-acting metabolite, OR-1896, in the treatment of cardiac ischemia.